(untitled) (Journal of Hama University, 2025)
This study aims to identify the relationship between academic adjustment and self-esteem and identify the differences between first and fourth year students in the Department of Curriculum and Educational Technologies at the College of Education - University of Damascus in academic adjustment and self-esteem according to the gender variable (males and females), and the academic year variable (first year and fourth year) The study sample consisted of (310) male and female students from the first and fourth years in the Department of Curricula and Educational Technologies at the College of Education - University of Damascus, distributed into (184) first years and (126) fourth years. They were selected in a stratified random way from the College of Education in University of Damascus, and they were administered an academic adjustment scale and a self-esteem scale prepared by the researcher. The results of the study indicated: - The presence of academic compatibility and self-esteem among members of the study sample to a moderate degree. - There is a statistically significant positive correlation between academic adjustment and self-esteem among members of the study sample, and the correlation value reached (0.72). - There are statistically significant differences between males and females in academic compatibility in favor of females. - There are statistically significant differences between males and females in self-esteem in favor of females. - There are statistically significant differences between first-year and fourth-year students in academic compatibility in favor of the fourth year. - There are statistically significant differences between first-year and fourth-year students in self-esteem in favor of the first year.